Fraud Hexagon Dalam Mendeteksi Financial Statement Fraud Pada Perusahaan Yang Terdaftar di Jakarta Islamic Index (JII) Periode 2020–2024 - Dea Aisia Nur Aini; Aida Nahar (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of the fraud hexagon on financial statement fraud in manufacturing companies listed on the Jakarta Islamic Index (JII) for the 2020–2024 period. The sample selection was conducted using the purposive sampling method, resulting in 23 companies out of 30 listed companies that met the research criteria, with a total of 115 observation data points. The criteria included the availability of complete annual reports in Rupiah currency and the presence of indications of fraud during the study period. Financial statement fraud was measured using the Beneish M-Score model, while the fraud hexagon variables were tested using logistic regression analysis. Partial test results showed that the financial target, proxied by Return on Assets (ROA), significantly influenced financial statement fraud, with a regression coefficient of 14.902 and a significance level of 0.031 (<0.05). In addition, rationalization, measured through total accruals, also had an effect.